2019
DOI: 10.3389/fpsyg.2019.02497
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance in Adolescent Students: The Role of Parenting Styles and Socio-Demographic Factors – A Cross Sectional Study From Peshawar, Pakistan

Abstract: Academic performance is among the several components of academic success. Many factors, including socioeconomic status, student temperament and motivation, peer, and parental support influence academic performance. Our study aims to investigate the determinants of academic performance with emphasis on the role of parental styles in adolescent students in Peshawar, Pakistan. A total of 456 students from 4 public and 4 private schools were interviewed. Academic performance was assessed based on self-reported gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 77 publications
2
27
0
1
Order By: Relevance
“…The emphasis should be placed on the guidance of self-cognition (Chen et al, 2020a). However, this study found the following: (1) facing the research of career exploration, more people pay attention to how graduates make the best choices, rather than looking for the reasons that make career choices difficult (Chan, 2018); (2) facing the development of high school students, more and more people choose to pay attention to academic achievements (Otte and Sharpe, 1979;Masud et al, 2019), family support (Pires et al, 2017), and school conditions (Lombardi et al, 2019). To sum up, although the attention to the career exploration of high school has risen in recent years, it is still difficult to maintain high attention and in-depth theoretical research, and many studies are borrowed from other research objects without considering the special situation of high school students.…”
Section: Not Enough Attention To the Career Exploration Of High Schoolmentioning
confidence: 95%
“…The emphasis should be placed on the guidance of self-cognition (Chen et al, 2020a). However, this study found the following: (1) facing the research of career exploration, more people pay attention to how graduates make the best choices, rather than looking for the reasons that make career choices difficult (Chan, 2018); (2) facing the development of high school students, more and more people choose to pay attention to academic achievements (Otte and Sharpe, 1979;Masud et al, 2019), family support (Pires et al, 2017), and school conditions (Lombardi et al, 2019). To sum up, although the attention to the career exploration of high school has risen in recent years, it is still difficult to maintain high attention and in-depth theoretical research, and many studies are borrowed from other research objects without considering the special situation of high school students.…”
Section: Not Enough Attention To the Career Exploration Of High Schoolmentioning
confidence: 95%
“…Different roles of mothers and fathers (Safyer, Volling, Schultheiss, & Tolman, 2018). Mother and father involvement in the school activities have influential to academic performance of child (Masud et al, 2019). The parents need to be involved in giving attention to the needs of children with learning resources and oversee the child's learning progress (Shunc, Pintich, & Mecee 2008).…”
Section: The Contribution Of Parents Attention To Student Achievement Motivationmentioning
confidence: 99%
“…On the other hand, the ethnic-cultural group could also be an important variable in the disparity of the different key competencies. That it is shown in relation to school success (Cvencek et al, 2018;Masud et al, 2019), social and emotional competencies (Kuo et al, 2020), reading comprehension (Sewasew & Koester, 2019), and mathematical competence (Assari et al, 2020;Kalaycioglu, 2015).…”
Section: Introductionmentioning
confidence: 99%